2017
DOI: 10.1289/ehp541
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Greenness, Impervious Surface Area, and Nighttime Lights on Biomarkers of Vascular Aging in Chennai, India

Abstract: Background:India is undergoing rapid urbanization with simultaneous increases in the prevalence of cardiovascular disease (CVD). As urban areas become home to an increasing share of the world’s population, it is important to understand relationships between the built environment and progression towards CVD.Objective:We assessed associations between multiple measures of the built environment and biomarkers of early vascular aging (EVA) in the Population Study of Urban, Rural and Semiurban Regions for the Detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 68 publications
7
31
0
1
Order By: Relevance
“…We estimated moderate increases in cardiometabolic risk factors in participants living in areas rapidly building up compared with areas where land use was stable. Our estimates for blood pressure were comparable to those from a cross-sectional study conducted in Chennai, India, evaluating the effect of residential surrounding greenness and impervious surfaces on markers of vascular aging (Lane et al 2017). Lane et al (2017) observed increases of 3.4% in SBP and of 1.5% in DBP for a 1-IQR decrease in NDVI.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We estimated moderate increases in cardiometabolic risk factors in participants living in areas rapidly building up compared with areas where land use was stable. Our estimates for blood pressure were comparable to those from a cross-sectional study conducted in Chennai, India, evaluating the effect of residential surrounding greenness and impervious surfaces on markers of vascular aging (Lane et al 2017). Lane et al (2017) observed increases of 3.4% in SBP and of 1.5% in DBP for a 1-IQR decrease in NDVI.…”
Section: Discussionsupporting
confidence: 78%
“…Our estimates for blood pressure were comparable to those from a cross-sectional study conducted in Chennai, India, evaluating the effect of residential surrounding greenness and impervious surfaces on markers of vascular aging (Lane et al 2017). Lane et al (2017) observed increases of 3.4% in SBP and of 1.5% in DBP for a 1-IQR decrease in NDVI. A recent meta-analysis showed a decrease in DBP of 2 mmHg in participants with the highest greenspace exposure vs. the lowest, estimated from 9,695 participants of 12 studies conducted in HICs (Twohig-Bennett and Jones 2018).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Vascular assessments were carried out using recommended guidelines, as described previously [19]. Blood pressure was measured on the right arm in the supine position using a validated oscillometric device (Model M5-I; Omron, Matsusaka, Japan) with appropriate cuff size.…”
Section: Measurementsmentioning
confidence: 99%
“…Village urbanisation was quantified using nighttime light intensity (NTLI), a data product derived from satellite sensors that capture visible near-infrared emissions from the earth's surface, which has been used to measure urbanisation and predict cardio-metabolic risk in several settings, including APCAPs cohort participants [19,20]. Geocoded village boundaries were applied to 2012 data from the Defense Meteorological Satellite Program (Operational Linescan System) accurate to a 1-km resolution, such that NTLI values represent emissions from the village areas only.…”
Section: Plos Medicinementioning
confidence: 99%